2014
DOI: 10.1080/10610278.2014.882511
|View full text |Cite
|
Sign up to set email alerts
|

Upper-rim calixarene phosphines consisting of multiple lower-rim OH functional groups: synthesis and characterisation

Abstract: The synthetic approaches to mono-isopropoxytrihydroxycalix[4]arenes bearing two or three diphenylphosphino groups at the upper macrocycle rim were elaborated. Due to reactive hydroxyl groups at the lower rim capable of binding with silica gel surface, the calixarenes, especially the enantiomerically pure inherently chiral diphosphinocalixarene, are promissing ligands for creation of hybride organic -inorganic metallocomplexing catalysts of organic (asymmetric) reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The number of reports on calixarenes is enormous, [93][94][95][96][97][98] they show results of theoretical studies, as well as practical applications of these compounds. Therefore an exhaustive presentation of studies dealing with calixarenes would be impossible, and in the review only selected examples are described.…”
Section: Discussionmentioning
confidence: 99%
“…The number of reports on calixarenes is enormous, [93][94][95][96][97][98] they show results of theoretical studies, as well as practical applications of these compounds. Therefore an exhaustive presentation of studies dealing with calixarenes would be impossible, and in the review only selected examples are described.…”
Section: Discussionmentioning
confidence: 99%
“…These products could be further brominated with N ‐bromosuccinimide (NBS; selective for phenolic rings) and then the sulfonyl group hydrolysed to give pure ICCs 3 which have potential as further building blocks. The authors themselves have reported a bisphosphine ICC 4 derived from this building block, although it is a very preliminary report and no application to asymmetric catalysis has yet been demonstrated …”
Section: Upper‐ and Lower‐rim Functionalisationmentioning
confidence: 99%
“…The authors themselves have reported ab isphosphine ICC 4 derived from this building block, although it is av ery preliminary report and no application to asymmetric catalysis has yet been demonstrated. [17] Boyko andK alchenko have also employed their more robust proximal alkylation strategy [16,19] using the chiral alkylating agent (R or S)-N-(1-phenylethyl)bromoacetamide (6) to generate lower-rim ICCs. [16,20] When alkylating am onopropoxy calix [4]arene, no diastereoselectivity was observed in the products.…”
Section: Upperand Lower-rim Functionalisationmentioning
confidence: 99%
See 2 more Smart Citations